PENGARUH PROFITABILITAS, AUDIT TENURE DAN SOLVABILITAS TERHADAP AUDIT DELAY (Studi pada Sektor Pertambangan yang terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Aditia, Rino Yuli (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to find out how profitability, audit tenure, and solvency affect audit delay in mining sector companies listed on the IDX for the 2018-2022 period. The variables to be tested in this study are audit tenure, profitability, solvency, as independent variables, while audit delay is the dependent variable. The population in this study are mining sector companies listed on the IDX for the 2018-2022 period, totaling 40 companies. The sample technique used in this study is purposive sampling, so the total sample is 11 companies with secondary data on financial reports for the 2018-2022 period. While the data analysis used in this study is multiple linear regression analysis. With the classical assumption test, partial test (t test), simultaneous test (F test) and test the coefficient of determination using the SPSS version 23 program. The results of the partial test show that audit tenure and solvency have an effect on audit delay, while profitability has no effect on audit delays. In addition, the results of the study simultaneously show that profitability, audit tenure, and solvency simultaneously influence audit delay. The magnitude of the explanation of tenure audit variables, profitability, solvency in providing an explanation for audit delay is 37.9%.